Tradisi Gotong Royong sebagai Cerminan Moderasi Beragama - Jihan Fauziah; Tasya Putri Padillah; Alfu Rijalul Ghoib; Iqbal Azwar Annas (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Strengthening religious moderation in Indonesia’s pluralistic society requires the optimisation of wisdom as a durable foundation for social harmony. One of the most deeply rooted cultural traditions reflecting collective solidarity is gotong royong (cooperation). In the context of increasing social fragmentation, identity politics, and religious polarisation, our cultural values are becoming increasingly relevant to reinforce inclusive and balanced religious expressions. Objective: This study aims to analyse the theoretical relationship between the tradition of gotong royong and religious moderation, and to explain how embedded cultural values shape inclusive, tolerant, and socially responsible religious practices. Method: This research employs a qualitative literature review, systematically examining 15 relevant peer-reviewed articles. The collected data were analysed analyzedntent analysis techniques to identify recurring themes, conceptual patterns, and theoretical linkages between cultural practices and religious moderation. Result: The findings reveal that gotong royong functions not merely as a communal activity but also as a value-laden social mechanism that internalises solidarity, equilibrium, and principles of collective responsibility, which resonate strongly with religious moderation. It also strengthens social cohesion and mitigates potential conflict in multicultural settings. Conclusion: The tradition of gotong royong constitutes a concrete manifestation of religious moderation grounded in local wisdom and plays a strategic role in sustaining social harmony. Contribution: This study reinforces a conceptual framework integrating local culture and religious moderation as a contextual, culturally embedded, and sustainable social strategy.